2006
DOI: 10.1080/00016480500504176
|View full text |Cite
|
Sign up to set email alerts
|

Does nasal septal surgery improve quality of life?

Abstract: In all, 285 patients (47.5%) responded. Analysis of the questionnaire showed an improvement in all disease-specific subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 18 publications
5
21
0
1
Order By: Relevance
“…The average age of our subjects was 38.6 years, with male patients being in majority (70.83%), which is in accordance with the results of other authors [6,12,13].…”
Section: Discussionsupporting
confidence: 93%
“…The average age of our subjects was 38.6 years, with male patients being in majority (70.83%), which is in accordance with the results of other authors [6,12,13].…”
Section: Discussionsupporting
confidence: 93%
“…Other causative conditions are: adenoid hypertrophy; turbinate hypertrophy; nasal tumors; and nasal polyps 1 . At present in the United States, 5 billion dollars are spent on medication to provide relief from nasal obstruction 2 . Nasal septum corrective surgery (septoplasty) was started in the 19 th century, and has been modified and improved since.…”
Section: Introductionmentioning
confidence: 99%
“…Silvoniemi et al similarly showed that nasal obstruction due to septal deviation is one of the most important etiologies of sleep-associated apnea (15). In this context, Schwentner, et al reported that septoplasty improves quality of life in patients with nasal septal deviation (16).…”
Section: Discussionmentioning
confidence: 99%